1979
DOI: 10.1530/jrf.0.0560075
|View full text |Cite
|
Sign up to set email alerts
|

Detection of early pregnancy in sheep by the rosette inhibition test

Abstract: The rossette inhibition test, an established test for determining the immunosuppressive potential of antilymphocyte serum, has been applied to the serum of sheep after mating. The rosette inhibition titre was much higher (12--26) in 7 sheep which were fertilized and remained pregnant for up to 21 days than in 5 sterile ewes mated with intact rams (8--10). The difference was apparent by 24 h after mating. One ewe had high titres for 6 days after mating but these then dropped and she returned to oestrus; early e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

1979
1979
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(41 citation statements)
references
References 8 publications
4
37
0
Order By: Relevance
“…The present study has not sought to focus upon the time of the first appearance of EPF which must await a more detailed study. However, it seems likely that it can be demonstrated within 24 h of mating, as with the other species so far tested (Morton et al, 1979a;Smart, Roberts, Clancy & Cripps, 1981 ;Rolfe, 1982). The fact that it was possible to hybridize EPF-A from the pig with EPF-B from another species to give full activity in vitro is in keeping with the lack of species specificity of EPF action on lymphocytes.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…The present study has not sought to focus upon the time of the first appearance of EPF which must await a more detailed study. However, it seems likely that it can be demonstrated within 24 h of mating, as with the other species so far tested (Morton et al, 1979a;Smart, Roberts, Clancy & Cripps, 1981 ;Rolfe, 1982). The fact that it was possible to hybridize EPF-A from the pig with EPF-B from another species to give full activity in vitro is in keeping with the lack of species specificity of EPF action on lymphocytes.…”
Section: Introductionmentioning
confidence: 85%
“…Antilymphocyte serum. Lymphocytes were obtained from the spleens of freshly killed male pigs, by the method described previously (Morton et al, 1979a). The lymphocytes were made up to 109 cells/ml in 0-9% NaCl, suspended in an equal volume of Freund's complete adjuvant (Difco, Detroit) and injected subcutaneously at multiple sites into outbred rabbits.…”
Section: Introductionmentioning
confidence: 99%
“…Further investigations demonstrated the appearance ofEPF in serum during pregnancy in all species studied and, although the time course varies, EPF can be found within 24-48 h of a fertile mating until at least the mid-term of pregnancy (Morton et al 1977(Morton et al , 1979a(Morton et al , 1979bNancarrow et al 1981;Smart et al 1982b;Koch et al 1983;Tinneberg et al 1984). During the preimplantation stage of pregnancy EPF is produced by maternal tissue in response to a signal from the conceptus, and its continuing presence is directly related to the presence of a fertilized ovum Cavanagh et al 1982).…”
Section: Introductionmentioning
confidence: 93%
“…The earliest time of detection in other species has not been extensively investigated but preliminary studies have shown that in humans, pigs and sheep, EPF is present in serum after 24-48 h (Morton et al 1979aNancarrow et al 1981;Rolfe, 1982). Thus the presence ofEPF in serum provides the earliest indication that fertilization has taken, place.…”
Section: Production Of Epfmentioning
confidence: 99%
See 1 more Smart Citation